2004
DOI: 10.1038/sj.bjp.0705982
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic, microscopic and biochemical characterisation of spontaneous colitis in a transgenic mouse, deficient in the multiple drug resistance 1a gene

Abstract: 4Biostatistics and Reporting, Sandwich, Kent 1 A novel animal model of spontaneous colonic inflammation, the multiple drug-resistant (mdr1) a À/À mouse, was identified by Panwala and colleagues in 1998. The aim of our study was to further characterise this model, specifically by measuring cytokines that have been implicated in inflammatory bowel disease (IBD) (IL-8 and IFN-g) in the colon/rectum of mdr1a À/À mice, and by determining the sensitivity of these, together with the macroscopic, microscopic and disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
37
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 69 publications
7
37
1
Order By: Relevance
“…They also indicated that infection with Helicobacter bilis induced diarrhea, weight loss, and IBDs in mdr1a-/-knockout mice. [14][15][16] Macroscopic, microscopic and biochemical examinations have confirmed that the colitis which develops in this model is similar to that of human IBDs, [14][15][16][17] and very recently, it has been confirmed that MDR1 mRNA expression in colonic tissues is down-regulated in patients with UC, but not with CD. 18) Next, MDR1 is located on chromosome 7 at q21.1, 19) which was one of the loci of susceptibility to…”
supporting
confidence: 65%
See 2 more Smart Citations
“…They also indicated that infection with Helicobacter bilis induced diarrhea, weight loss, and IBDs in mdr1a-/-knockout mice. [14][15][16] Macroscopic, microscopic and biochemical examinations have confirmed that the colitis which develops in this model is similar to that of human IBDs, [14][15][16][17] and very recently, it has been confirmed that MDR1 mRNA expression in colonic tissues is down-regulated in patients with UC, but not with CD. 18) Next, MDR1 is located on chromosome 7 at q21.1, 19) which was one of the loci of susceptibility to…”
supporting
confidence: 65%
“…14-16) Macroscopic, microscopic and biochemical examinations have confirmed that the colitis which develops in this model is similar to that of human IBDs, [14][15][16][17] and very recently, it has been confirmed that MDR1 mRNA expression in colonic tissues is down-regulated in patients with UC, but not with CD.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Interestingly, saline treatment seems to activate the HPA axis in the abcb1ab (À/À) mice, but not in FVB/N controls. This may be due to the fact that abcb1ab (À/À) mice suffer from spontaneous colitis (Banner et al, 2004) and, therefore, could be more sensitive to the manipulation associated with two daily i.p. injections for 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…-/-) spontaneously develop colitis with characteristics including dysregulated epithelial cell growth and leukocytic infiltration into the lamina propria of the large intestine; 20 weeks is the average age at onset [1,2,4,7,10,15,16,20]. In a previous study, we found that a series of Senescence-Accelerated Mouse (SAM) strains, including SAMR1, SAMP1, and SAMP6, have a spontaneous loss-of-function mutation in the Abcb1a gene [24].…”
Section: Abcb1amentioning
confidence: 99%